Gastropod Community Structure in the Mangrove Area, Kuala Batee District, Southwest Aceh District - Rahmi, Mira Mauliza; Farija, Nurul; Lisdayanti, Eka (Journal of Coastal and Ocean Sciences, 2024)
This research was conducted to determine the types of gastropods and the structure of the gastropod community in the Mangrove area of Kuala Batee District, Southwest Aceh Regency. The quantitative descriptive method is used to determine research stations using purposive sampling techniques. Gastropod sampling was carried out at three station locations, each station consisting of three sub-stations with a size of 10 x 10 m. In the substations, 15 transects measured 1 x 1 m, namely, two points at the corner of each transect and one point in the middle. The results of the research showed that the gastropods found were 11 species from 4 ordo, ordo Archaeogastropoda consists of Neritina turita, N.semiconica, N.variegate, Neritodryas dubia, and Clithon corona, ordo Ceanogastropoda consists of Faunus ater and Bitium munitum, ordo Mesogastropoda consists of Cerithidea optusa, Stenomelania plicaria, and Thiara scabra, ordo Ellobiida consist of Cassidula angulifera. The structure of the gastropod community in the mangrove area of Kuala Batee District, Southwest Aceh Regency, has a diversity index ranging from 0.65-1.32, including the medium category, uniformity index values ranging from 0.36-0.63 including the medium category, and dominance values ranging from between 0.33-0.63 is included in the medium category. Environmental parameters in the mangrove area show an average temperature value of 28.20C, a salinity value of 5.6 ppt, and a pH value of 8.3